AdS/CFT correspondence : (European Mathematical Society, 2005)
On the physical this book provides a duality between a theory of quantum gravity and a field theory. The mathematical counterpart is the relation between Einstein metrics and their conformal boudaries. The correspondence has been intensively studied, and a lot of progress emerged from the confrontation of viewpoint between mathematics and physics.